Antimicrobial Activity of Plant Extracts against Bacillus Subtilis, Staphylococcus Aureus and Escherichia Coli - Liliwirianis N; Wan Zuraida Wan Mohd Zain; Jamaluddin Kassim; Shaikh Abdul Karim (E-Journal of Chemistry)
Local herbs have many potential that may be active with antimicrobial activity. A screening was conducted with 11 species of herbs collected in UiTM Pahang Forest Reserve. Epipremnum sp., Zingiber sp. Tetracera indica, Tectaria crenata, Piper stylosum, Homalomena propinque, Goniothalamus sp., Elephantopus scaber, Mapania patiolale, Melastoma sp., Stemona tuberosa, Phullagathis rotundifolia, Thotea grandifolia and Smilax sp. were extracted with methanol to obtain their crude. The agar diffusion method using blank disc of 6 mm diameter were loaded with 1000 µg/mL of methanol crude and applied to the inoculate plate was used to assess the antimicrobial activity against two gram positive bacteria (Bacillus subtilis and Staphylococcus aeureus) and one gram negative bacteria (Escherichia coli). The results evaluated as the diameter of the inhibition zone of microbial growth, showed that all the extracts were active against gram-positive bacteria and gram-negative bacteria. The extract of Stemona tuberose was found to be the most active against the E. coli and S. aeureus while Piper stylosum active against B. subtilis.